Condition of adaptation process of the student to training in building university - A Yu Sidelnikov (RUDN Journal of Ecology and Life Safety, 2012)
In article it is considered aspects of psychological adaptation of students-building of specialities at the vocational training initial stage. Are shown with what psychological difficulties there are first-year students in building high school. The analysis of three groups of students of I course on degree of psychological adaptation to training conditions in high school is carried out.